VD_FINDINFO 45/2012 vom 21. Januar 2013 - VD Tribunal cantonal (2013)
RÉCUSATION, JONCTION DE CAUSES, COMPOSITION DE L'AUTORITÉ | 6 al. 1 let. a ROTC, 10 al. 2 LPA-VD, 11 al. 3 LPA-VD, 24 al. 1 LPA-VD, 9 let. e LPA-VD